1970
DOI: 10.1128/jb.104.3.1052-1064.1970
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cell Division inEscherichia coli:Characterization of Temperature-Sensitive Division Mutants

Abstract: A temperature-sensitive division mutant of Escherichia coli was isolated by using differential filtration to select for filaments at 42 C and normal cells at 30 C. Cells shifted from 30 to 42 C stop dividing almost immediately, suggesting the temperature-sensitive element is required for cell division late in the cell cycle. Cells returned to 30 from 42 C divide abruptly, suggesting accumulation of division potential at 42 C. Inhibitors of protein, deoxyribonucleic acid, and ribonucleic acid synthesis do not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
54
1

Year Published

1972
1972
1994
1994

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 31 publications
9
54
1
Order By: Relevance
“…In the third case (ftsB, C, F, and G mutants), the incubation at high temperature causes rapid and irreversible damage to the division mechanism of the mutant cells. Similar mutants of these types have been described previously (1,17,18,26,29,30,40).…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…In the third case (ftsB, C, F, and G mutants), the incubation at high temperature causes rapid and irreversible damage to the division mechanism of the mutant cells. Similar mutants of these types have been described previously (1,17,18,26,29,30,40).…”
Section: Resultssupporting
confidence: 67%
“…Therefore, as has already been shown by Kirby et al (25), filament formation and A induction can be a related process (42), but the arrest of cell division of fts mutants per se is not the cause of prophage induction. The correction of various phenotypes of E. coli mutants by the addition of salts or sucrose to the growth medium has already been reported (29)(30)(31)(32)36). A similar effect has been described in the case of auxotrophic mutants of yeast (9).…”
Section: Resultsmentioning
confidence: 53%
“…Clearly, this form of the FtsA protein is irreversibly inactivated, and this inactivation must be essentially Instantaneous. Reeve et al (1970) measured the half-life of the FtsA6 protein at 42°C and found it to be approximately 3 minutes: we have confirmed this (data not shown). A surprising observation is that there Is a long delay between the return to SCC and the resumption of division: no division takes place at all for the first 90-120 minutes, by which time the mass of the cells has approximately doubled.…”
Section: Figures 1 (A) and (B)supporting
confidence: 70%
“…Synthesis of material cross-reacting with anti-galactose-binding protein antibodies occurred during cell division but not during cell elongation. Similar observations were made in BUG-6, a mutant which is temperature sensitive for cell division (Reeve et al, 1970). This strain synthesized galactose-binding protein only at the permissive temperature (Shen and Boos, 1973).…”
supporting
confidence: 54%
“…When shifted t o 42"C, division stops immediately and long filaments form. The mutation does not affect DNA replication but prevents septum formation (Reeve et al, 1970). the periplasmic shock proteins released from both cultures revealed the following: Both preparations contained large amounts of material that in the immunodiffusion technique cross-reacts with anti-GLPT antibodies.…”
mentioning
confidence: 94%